Kesiapan Pedagogis Mahasiswa dalam Keterampilan Opening dan Closing Instruction pada Mata Kuliah Pembelajaran Mikro: Pedagogical Readiness of Students in Opening and Closing Instruction Skills in a Microteaching Course - Ismail Marzuki; Aliurridha Aliurridha; Muh. Khairussibyan (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This study aims to describe students’ pedagogical readiness in opening and closing instruction skills in the Microteaching course. The study employed a qualitative descriptive method, with data collected through observations of students’ teaching practices using a teaching skills assessment instrument. The research subjects were students enrolled in the Microteaching course in the Indonesian Language and Literature Education Study Program. The data were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings reveal that, in general, students demonstrated Farly good pedagogikah readiness in opening instruction skills, particularly in attracting students’ attention, delivering greetings, and explaining learning objectives. However, several weaknesses were still identified in closing instruction skills, such as the lack of optimal reflective activities, reinforcement of learning materials, and the delivery of follow-up activities. These findings indicate that microteaching plays an important role in developing the pedagogical competencies of prospective teachers, particularly in constructing effective, communicative, and reflective learning structures before engaging in actual classroom teaching practices.